Vascularized Composite Allograft Rejection Is Delayed by Intrajejunal Treatment with Donor Splenocytes without Concomitant Immunosuppressants - Christopher Glenn Wallace; Chia-Hung Yen; Hsiang-Chen Yang; Chun-Yen Lin; Ren-Chin Wu; Wei-Chao Huang; Jeng-Yee Lin; Fu-Chan Wei (Clinical and Developmental Immunology)
Background. Mucosal or oral tolerance, an established method for inducing low-risk antigen-specific hyporesponsiveness, has not been investigated in vascularized composite allograft (VCA) research. We studied its effects on recipient immune responses and VCA rejection. Methods. Lewis rats (; TREATED) received seven daily intrajejunal treatments of splenocytes from semiallogeneic Lewis-Brown-Norway rats (LBN) or vehicle (; SHAM). Recipients’ immune responses were assessed by mixed lymphocyte reaction (MLR) against donor antigen and controls. Other Lewis (; TREATED/VCA) received LBN hindlimb VCA and daily intrajejunal treatments of LBN splenocytes, or LBN VCA without treatment (; SHAM/VCA), until VCAs rejected. Recipients’ immune responses were characterised and VCAs biopsied for histopathology. Immunosuppressants were not used. Results. LBN-specific hyporesponsiveness was induced only in treated Lewis recipients. Treatment significantly reduced MLR alloreactivity, significantly reduced VCA rejection on histopathology, and significantly delayed clinical VCA rejection (; TREATED/VCA mean 9.6 versus 6.0 days for SHAM/VCA). Treatment significantly increased immunosuppressive IL-10/IL-4/TGF-β production and significantly decreased proinflammatory IFN-γ/TNF-α. Conclusion. Jejunal exposure to antigen conferred donor specific hyporesponsiveness that delayed VCA rejection. This method may offer a low-risk adjunctive treatment option to help protect VCAs from rejection.